Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, and Monocyte-to-Lymphocyte Ratio in Depression: An Updated Systematic Review and Meta-Analysis - Cheng, Yanwei; Wang, Yiwen; Wang, Xiangyi; Jiang, Zhuoya; Zhu, Lijun; Fang, Shaokuan (Frontiers in Psychiatry, 2022)
Background: Research on neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR) in depression is still emerging and has increased three-fold since the first meta-analysis. An updated meta-analysis with sufficient studies can provide more evidence for a potential relationship between NLR, PLR, MLR, and depression. Methods: We identified 18 studies from the PubMed, EMBASE, Cochrane library, and Web of Science databases. Meta-analyses were performed to generate pooled standardized mean differences (SMDs) and 95% confidence intervals (CIs) between patients with depression and controls. Sensitivity analysis, subgroup analysis, meta-regression, and publication bias were conducted. Results: A total of 18 studies including 2264 depressed patients and 2415 controls were included. Depressed patients had significantly higher NLR and PLR compared with controls (SMD=0.33, 95% CI: 0.15 – 0.52, p <0.001 and SMD=0.24, 95% CI: 0.02 – 0.46, p <0.05, respectively). MLR was slightly higher in depressed individuals compared to controls (SMD=0.15, 95% CI: -0.26 - 0.55, p >0.05), despite the absence of significance. Sensitivity analysis removing one study responsible for heterogeneity showed a higher and significant effect (SMD=0.32, 95% CI: 0.20 – 0.44) of MLR. Three subgroup analyses of NLR, PLR, MLR, and depression revealed obvious differences in the inflammatory ratios between depressed patients and controls in China and the matched age and gender subgroup. Individuals with PSD had higher NLR and MLR values as compared to non-PSD patients (SMD=0.51, 95% CI: 0.36-0.67, p <0.001 and SMD=0.46, 95% CI: 0.12-0.79, p <0.01, respectively). Meta-regression analyses showed that male proportion in the case group influenced the heterogeneity among studies that measured NLR values (p <0.05). Conclusions: Higher inflammatory ratios, especially NLR, are significantly associated with an increased risk of depression. In the subgroup of China and matched age and gender, NLR, PLR, and MLR were all elevated in depressed patients versus controls. Individuals with PSD had higher NLR and MLR values as compared to non-PSD patients. Gender differences might have an effect on NLR values in patients with depression.